Penerapan whistleblowing system di instansi pemerintah sebagai inisiatif gerakan antikorupsi di Indonesia - Agus Joko Pramono; Mohamad Iqbal Aruzzi (Komisi Pemberantasan Korupsi, 2023)
Whistleblowing is viewed as a powerful tool to identify corruption. Apart from motivation, beha-viour, and the rights of whistleblower protection, as success factors of whistleblowing programs, current research argues that it is hard to expect the emergence of whistleblowers if channels to report wrongdoing do not exist. Hence, the purpose of this study is to explore and explain the provision of whistleblowing policy and the range of whistleblowing systems and their channels as an anti-corruption initiative in Indonesian government institutions. The research utilised content analysis from secondary data and analys-ed primary data obtained through online survey completed by government auditors working in Indonesian government institutions. Indonesia has at least 618 government institutions, whereby the researcher chose the most “valuable” sample based on a hierarchy of 104 institutions from central government and provincial level; it excludes government institutions at the district and municipal level, 44 questionnaires were returned and usable (42% response rate). The research found that from these institutions, just a few have had a policy that aligned with international best practice, some were not even backed up by a policy at all. It appears that many institutions have built a whistleblowing system for lip service only; they do not provide a comprehensive policy to protect the witness, handle the report, or guarantee an investigation. Research outcomes are expected to encourage the Indonesian government to extend whistleblowing provisions in their institutions. This study can be useful as well for government institutions to get a general idea of the common content of whistleblowing policies.